Design and Optimization of Itraconazole Tablet Employing Solid Dispersion Approach - Savjani, Ketan (Asian Journal of Pharmaceutics (AJP), 2017)
Introduction: The present research was envisaged for the development of ternary solid dispersion for enhancement of solubility and dissolution rate of itraconazole, a highly hydrophobic antifungal agent. Materials and Methods: The objective was strived through spray drying technique amalgamated with experiment design approach. Initially, trials were taken with different hydrophilic carriers to prepare binary amorphous system; however, selected levels of polymers were found to be incompetent to offer desired drug solubility or dissolution rate. Hence, combinations of different hydrophilic carriers were explored for development of spray dried ternary amorphous system employing full factorial design as an experimental tool. Results and Discussion: The developed ternary system was found to be completely amorphous as demonstrated by spectral and thermal analyses and substantially enhanced drug solubility and dissolution rate. Finally, the developed amorphous system was formulated into a tablet dosage form with substantially enhanced drug dissolution rate as compared to that of the crystalline form and found to be stable under both accelerated and controlled storage condition with statistically predicted shelf life of more than 60 months. Conclusion: The research evidently exemplifies enhancement of solubility and dissolution rate of stated model drug through spray drying technique and emphasizes criticality of ternary system in the formulation of amorphous solid dispersion.